(untitled) (Research, Society and Development, 2023)
Pará was one of the states in Brazil most affected by the Coronavirus pandemic, especially due to demographic, health infrastructure and socioeconomic differences between its 13 Health Regions. This article aims to present the epidemiological profile of Covid-19 and potential correlations with the demographic, socioeconomic and health services profile in the 144 municipalities of the 13 Health Regions of Pará. This is a cross-sectional, descriptive, quantitative, and qualitative study, with the years 2020, 2021 and 2022 as a time frame. It was observed that 2020 was the year with the highest number of cases of Covid-19 in Pará, while 2021 had the highest number of deaths. Correlation analyzes between Covid-19 Mortality Rate and socioeconomic and demographic variables proved to be weak, due to potential bias in socioeconomic data and the high complexity of the test.